1989
DOI: 10.1159/000261168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mouthrinse Containing Calcium Lactate on the Formation and Mineralization of Dental Plaque

Abstract: In this study, a mouthrinse containing calcium lactate was tested for its effect on the accumulation of dental plaque and on the concentrations of calcium and phosphorus therein. Human volunteers rinsed four times per day with a calcium lactate (165 mmol/l) solution for 1 week. Plaque samples, collected 16 h after the last rinse, were analyzed chemically. Calcium lactate rinses had no effect on the plaque score, but resulted in approximately twofold increases of calcium and phosphorus in plaque. The incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In principle, the chemical properties of this interface can be altered to decrease the cariogenic challenge originating from the metabolism of the oral flora. Several agents have been advanced as constituents of mouthwashes to minimize enamel demineralization, for example, lactate dehydrogenase [Higham and Edgar, 1991], urea and fluoride [Pearce, 1982[Pearce, , 1984Pearce and Nelson, 1988;Pearce et al, 1991], calcium phosphate [Stralfors, 1964;Rankine et al, 1989], calcium lactate [van der Hoeven, 1985;Shrestha et al, 1982;van der Hoeven et al, 1989;Kashket and Yaskell, 1992], calcium glycerophosphate [Bowen, 1972;Grenby and Bull, 1975;Sidi and Wilson, 1991] …”
mentioning
confidence: 99%
“…In principle, the chemical properties of this interface can be altered to decrease the cariogenic challenge originating from the metabolism of the oral flora. Several agents have been advanced as constituents of mouthwashes to minimize enamel demineralization, for example, lactate dehydrogenase [Higham and Edgar, 1991], urea and fluoride [Pearce, 1982[Pearce, , 1984Pearce and Nelson, 1988;Pearce et al, 1991], calcium phosphate [Stralfors, 1964;Rankine et al, 1989], calcium lactate [van der Hoeven, 1985;Shrestha et al, 1982;van der Hoeven et al, 1989;Kashket and Yaskell, 1992], calcium glycerophosphate [Bowen, 1972;Grenby and Bull, 1975;Sidi and Wilson, 1991] …”
mentioning
confidence: 99%
“…In testing the effects of mouthrinses containing calcium lactate on the levels of plaque calcium, reduced calculus deposition was observed in healthy volunteers [Schaeken and van der Hoeven, 1990], This was a rather unexpected finding, since approximately twofold in creased levels of calcium in dental plaque were observed even 16 h after rinses with calcium lactate [van der Hoeven et al, 1989;Schaeken and van der Hoeven, 1990]. The present experiment was undertaken to retest the antical culus properties of calcium lactate.…”
Section: Introductionmentioning
confidence: 77%
“…A clue to its possible mode of action can be drawn from the work of Van der Hoeven et al (1989), who found that use of a 1 % calcium lactate mouthrinse 4 times a day failed to alter gross plaque accumulation, but did double plaque calcium and interestingly also phosphate levels after only one week's usage. A clue to its possible mode of action can be drawn from the work of Van der Hoeven et al (1989), who found that use of a 1 % calcium lactate mouthrinse 4 times a day failed to alter gross plaque accumulation, but did double plaque calcium and interestingly also phosphate levels after only one week's usage.…”
Section: Calcium Lactatementioning
confidence: 99%